Dystopia in the world of utopia: Unsustainable realities of sustainably themed expositions - Schrenk, Lisa; Jensen, Melissa (ARCC Conference Repository, 2014)
Since the 1970s international expositions have celebrated advances in science and technology as potential ways to lessen modern man's impact on Earth's natural resources. Expositions held in the past couple of decades have presented themes that more directly relate to issues of sustainability. This paper explores the disconnect that exists between the utopian ideas promoted at these "sustainable” expositions and the dystopic realities of the events themselves. In particular, it does this by revealing how both the immense quantity of resources used in the creation and operation of these short-lived events and the decomposing remnants left behind after closing day present tangible evidence of the failure of "sustainable” expositions to reflect fully the fundamental principles that organizers set out to disseminate at these grand, festive events.